Study of interference alignment for wireless communications - Yang, Mark Wei Wen (2013)
With the recent introduction of interference alignment (IA) technique in multiple input multiple output (MIMO) system, the communication system is thus able to increase in it data throughput, signal quality and signal coverage. The interference alignment technique combined the transmitter precoding as well as receiver interference suppression to align and cancel out the co-users interference in MIMO system. In this final year project report, we will study various IA algorithms which design the precoders and the interference suppressions, using MATLAB program to simulate the performance of each algorithms with aspect to its bit error rate (BER). As IA needed perfect channel information to fully cancel out all interferences which is not realistic in real life, we will also simulate the algorithms with imperfect channel knowledge to fully understand the feasibility of the IA technique.